“Switch-Off” of Respiratory Sinus Arrhythmia Can Occur in a Minority of Subjects During Functional Magnetic Resonance Imaging (fMRI) - Rassler, Beate; Schwerdtfeger, Andreas; Aigner, Christoph Stefan; Pfurtscheller, Gert (Frontiers in Physiology, 2018)
A group of 23 healthy scanner naïve participants of a functional magnetic resonance imaging (fMRI) study with increased state anxiety exhibited 0.1-Hz oscillations in blood-oxygenation-level-dependent (BOLD) signals, heart rate (HR) beat-to-beat intervals (RRI) and respiration The goal of the present paper is to explore slow oscillations in respiration and RRI and their phase-coupling by applying the dynamic “wave-by-wave” analysis. Five participants with either high or moderate levels of fMRI-related anxiety (age 23.8  3.3y) were found with at least one bulk of consecutive breathing waves with a respiration rate between 6 to 9 breaths/min in a 5-minute resting state. The following results were obtained: (i) Breathing oscillations with dominant frequencies at 0.1 Hz and 0.15 Hz displayed a 1:1 coupling with RRI. (ii) Inspiration time was significantly longer than expiration time. (iii) RRI minima (start of HR decrease) coincided with the early inspiration, and RRI maxima (start of HR increase) coincided with the late inspiration. (iv) RRI rhythm led over the respiratory rhythm. This phase-coupling pattern is quite contrary to typical respiratory sinus arrhythmia where HR increases during inspiration and decreases during expiration. The results support the assumption that not only an increased respiration rate but also slow breathing may play a role in anxiety processing.